2018
DOI: 10.1017/s0021932017000700
|View full text |Cite
|
Sign up to set email alerts
|

Do Biomarkers Vary by Social Class, Education and Region and Is Migration Important? Evidence From a Cohort of British Adults

Abstract: The aim of this study was to test whether Body Mass Index (BMI), waist circumference, systolic and diastolic blood pressure, Forced Expiratory Volume (FEV1) and Peak Expiratory Flow (PEF) vary in relation to social class at birth and adulthood, educational level and region of residence, and also with inter-generational social, educational and regional mobility/migration. The study used 5702 adults (2894 males and 2718 females) from the longitudinal British National Child Development Study (all children born in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 83 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…In contrast to indices such as the Area Deprivation Index (ADI), which summarizes contemporary neighborhood exposures, our Adversity-Opportunity Index (AOI) incorporates the measurement of historic, cumulative experiences, focused at the individual level. Paralleling prior work (21), we equally weighted and summed household income (22), education (23), in utero tobacco smoke exposures (24), occupational respiratory exposures (25), and access to fresh and healthy food (26,27) as five representative indicators of social and structural determinants of health to create the AOI. Lower scores represent more adverse conditions.…”
Section: Adversity-opportunity Indexmentioning
confidence: 99%
“…In contrast to indices such as the Area Deprivation Index (ADI), which summarizes contemporary neighborhood exposures, our Adversity-Opportunity Index (AOI) incorporates the measurement of historic, cumulative experiences, focused at the individual level. Paralleling prior work (21), we equally weighted and summed household income (22), education (23), in utero tobacco smoke exposures (24), occupational respiratory exposures (25), and access to fresh and healthy food (26,27) as five representative indicators of social and structural determinants of health to create the AOI. Lower scores represent more adverse conditions.…”
Section: Adversity-opportunity Indexmentioning
confidence: 99%
“…Occupational respiratory exposure was recorded as never, ever, or unsure [23,24]. Maximal educational attainment [25] was recorded as less than high school diploma, greater than higher school diploma, or high school diploma. Household income was reported as high, low, or unreported, with a threshold set at $50 000/year to approximate 200% of the federal poverty line for a family of four [26,27].…”
Section: Socio-environmental Exposuresmentioning
confidence: 99%
“…Recent longitudinal and cross-sectional research suggests that upward, or positive, change in SES from childhood to adulthood (i.e., upward mobility [UM]), may mitigate some of these negative effects (11,13,(19)(20)(21)(22)(23). Conversely, downward SES mobility (or negative change in SES from childhood to adulthood) has been found to be associated with negative mental health, physical health, and cognitive outcomes (e.g., Refs.…”
Section: Introductionmentioning
confidence: 99%
“…(11,19,22)). For example, a study in the United Kingdom found that upward changes in SES were related to better cardiovascular and respiratory health outcomes, whereas downward changes in SES were associated with poorer health outcomes (21). Another large study using Health and Retirement Study data found that those who experienced UM from childhood to adulthood had fewer depressive symptoms, better cognitive functioning (based on a telephone screen), and fewer chronic health conditions than those with similar childhood SES who did not experience UM (11).…”
Section: Introductionmentioning
confidence: 99%